1999
DOI: 10.1016/s0896-6273(00)80776-x
|View full text |Cite
|
Sign up to set email alerts
|

F-Spondin Is Required for Accurate Pathfinding of Commissural Axons at the Floor Plate

Abstract: The commissural axons project toward and across the floor plate. They then turn into the longitudinal axis, extending along the contralateral side of the floor plate. F-spondin, a protein produced and secreted by the floor plate, promotes adhesion and neurite extension of commissural neurons in vitro. Injection of purified F-spondin protein into the lumen of the spinal cord of chicken embryos in ovo resulted in longitudinal turning of commissural axons before reaching the floor plate, whereas neutralizing anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
97
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 46 publications
3
97
1
1
Order By: Relevance
“…F-spondin promotes adhesion and outgrowth of commissural axons and inhibits adhesion of neural crest cells. Consistent with this, in vivo perturbation experiments demonstrate that F-spondin is required both for accurate guidance of commissural axons at the floor plate (13) and for restriction of migration of neural crest cells (14). Blocking of the endogenous F-spondin in ovo causes: (i) lateral drifting of commissural axons at the contralateral floor plate boundary; (ii) neural crest cell migration into otherwise inhibitory domains such as the caudal somite, the ventral medial sclerotome, and the dermomytome; and (iii) widening of the ventral root at the sclerotome level.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…F-spondin promotes adhesion and outgrowth of commissural axons and inhibits adhesion of neural crest cells. Consistent with this, in vivo perturbation experiments demonstrate that F-spondin is required both for accurate guidance of commissural axons at the floor plate (13) and for restriction of migration of neural crest cells (14). Blocking of the endogenous F-spondin in ovo causes: (i) lateral drifting of commissural axons at the contralateral floor plate boundary; (ii) neural crest cell migration into otherwise inhibitory domains such as the caudal somite, the ventral medial sclerotome, and the dermomytome; and (iii) widening of the ventral root at the sclerotome level.…”
supporting
confidence: 57%
“…F-spondin, a secreted adhesion molecule expressed in the embryonic floor plate of vertebrates (9)(10)(11)(12)(13), and the caudal somite of birds (14), plays a similar dual role in patterning the nervous system. F-spondin promotes adhesion and outgrowth of commissural axons and inhibits adhesion of neural crest cells.…”
mentioning
confidence: 99%
“…SPON1, a member of the spondin family of genes, is highly expressed in the embryonic neural floor plate, and it is essential for neural growth and cell adhesion (16,17). Prior studies implicate this same gene in brain structural development and neural connectivity, and its expression declines with aging (18).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it was also shown that repeated injection of the TSR fusion proteins into the central canal of chick embryos prevented many commissural axons from crossing the midline. Consequently, these axons were observed to turn orthogonally at the ipsilateral margin of (or within) the floor plate (Burstyn-Cohen et al, 1999). Thus, it appears that positive interactions between F-spondin and an as yet unidentified receptor(s) are also required for midline crossing in the chick spinal cord.…”
Section: Vertebrate Spinal Cordmentioning
confidence: 96%
“…F-spondin, an extracellular matrix protein that was originally identified in a subtractive hybridization screen for cDNAs encoding proteins enriched in the embryonic rat floor plate, is produced and secreted by floor plate cells (Klar et al, 1992). More recently, a chick homolog of F-spondin has been identified and soluble fusion proteins representing the thrombospondin type I repeat (TSR)-containing domain of this protein have been shown to bind to, and promote the outgrowth of, commissural growth axons in vitro (Burstyn-Cohen et al, 1999). In addition, it was also shown that repeated injection of the TSR fusion proteins into the central canal of chick embryos prevented many commissural axons from crossing the midline.…”
Section: Vertebrate Spinal Cordmentioning
confidence: 99%